Pengaruh Pemanfaataan Sistem Keuangan Desa, Kejelasan Sasaran Anggaran, Dan Kemampuan Pemanfaatan Teknologi Informasi Terhadap Keberhasilan Pengelolaan Dana Desa (Studi Pada Desa Se-Kecamatan Langsa Lama Kota Langsa) - Aldi Saputra; Nasrul Kahfi Lubis; Afrah Junita (LPPM Universitas Labuhanbatu, 2023)
This study aims to determine the effect of using the village financial system, clarity of budget targets, and the ability to use information technology on the successful management of village funds. This research is a quantitative study using primary data types obtained from questionnaires and measured using a Likert scale. The population in this study used all villages in the Langsa Lama sub-district as village heads of 15 villages. The sampling technique used stratified random sampling. The sample criteria in this study were the village head, village secretary, village treasurer, and siskeudes operators in Langsa Lama District, totaling 60 people. The data analysis technique in this study used multiple linear regression analysis with the help of SPSS version 25. The results of this study indicate that the variable use of the village financial system has a positive and significant effect on the success of managing village funds, the variable clarity of budget targets has a positive and significant effect on success management of village funds, as well as the variable ability to use information technology has a positive and significant effect on the successful management of village funds. Based on the limitations in this study, it is recommended that future researchers who wish to examine the successful management of village funds add other variables related to the successful management of village funds, for example budget participation, competence of village officials and others. Conduct research in other areas or in different areas. More wider. Suggestions for each village government must increase the transparency of the use of the budget and in the preparation must include people who are components.